Säästöpuut vetävät puoleensa tukkimiehentäit - Viiri, Heli (Metsäntutkimuslaitos, 2008)
Selostus artikkelista: Pitkänen, A., Kouki, J., Viiri, H. & Martikainen, P. 2008. Effects of controlled forest burning and intensity of timber harvesting on the occurrence of pine weevils, Hylobius spp., in regeneration areas. Forest Ecology and Management 255: 522-529.
Keywords: avohakkuu; kulotus; säästöpuu; tukkimiehentäi